Microbial Siderophores: A New Insight on Healthcare Applications - Shilpa Borehalli Mayegowda; Manjula Nagalapur Gadilingappa (BME Frontiers)
Globally, increased illness and disorders have gained importance in improvising therapeutics to help extend the lifespan of an individual. In this scenario, understanding the mechanism of bacterial pathogenicity linked to the interaction between the host and the pathogen focusing on essential metal ions is necessary. Numerous studies indicate that the severity of a disease might be due to the reduced availability of iron, linked to abnormal production or lack of acquisition systems. However, several microbes produce siderophores as virulence factors, low-molecular-weight organic compounds for acquisition of iron by iron-chelating systems. In medical applications, siderophores are employed in novel strategies in order to design effective new drugs and vaccines, targeting and delivering antibiotics to target sites in multidrug-resistant pathogens. Meanwhile, some types of siderophores are used as drug delivery modalities and antimalarial, anticancer, and antibacterial agents, for example, by employing conjugation techniques such as Trojan horse delivery. Hence, the current review integrates several applications of siderophores with an overview covering taxonomy, organisms producing iron affinity carriers, and their acquisition mechanism. This understanding may delineate newer opportunities to adapt possible therapies and/or treatments against several multidrug-resistant pathogens, representing a crucial solution for public health problems worldwide.